Testing time for Islamic banking and finance - Khaliq, Ahmad (2016)
The question whether Islamic Banking Services can sustain itself in a volatile sector that's going from bad to worse needs an answer.The conventional financial system has gone through many tests and is still sustaining, though business confidence in major economies - the US, Europe and Japan – has been plummeting.The article addresses the above issue.